Responses to heat waves: what can Twitter data tell us? - Zander, Kerstin K.; Rieskamp, Jonas; Mirbabaie, Milad; Alazab, Mamoun; Nguyen, Duy (Natural Hazards)
Abstract Increasing average temperatures and heat waves are having devasting impacts on human health and well-being but studies of heat impacts and how people adapt are rare and often confined to specific locations. In this study, we explore how analysis of conversations on social media can be used to understand how people feel about heat waves and how they respond. We collected global Twitter data over four months (from January to April 2022) using predefined hashtags about heat waves. Topic modelling identified five topics. The largest (one-third of all tweets) was related to sports events. The remaining two-thirds could be allocated to four topics connected to communication about climate-related heat or heat waves. Two of these were on the impacts of heat and heat waves (health impacts 20%; social impacts 16%), one was on extreme weather and climate change attribution (17%) and the last one was on perceptions and warning (13%). The number of tweets in each week corresponded well with major heat wave occurrences in Argentina, Australia, the USA and South Asia (India and Pakistan), indicating that people posting tweets were aware of the threat from heat and its impacts on the society. Among the words frequently used within the topic ‘Social impacts’ were ‘air-conditioning’ and ‘electricity’, suggesting links between coping strategies and financial pressure. Apart from analysing the content of tweets, new insights were also obtained from analysing how people engaged with Twitter tweets about heat or heat waves. We found that tweets posted early, and which were then shared by other influential Twitter users, were among the most popular. Finally, we found that the most popular tweets belonged to individual scientists or respected news outlets, with no evidence that misinformation about climate change-related heat is widespread.
Keywords: Earth and Planetary Sciences (miscellaneous); Atmospheric Science; Water Science and Technology

Crisis Communication on Twitter: Differences Between User Types in Top Tweets About the 2015 “Refugee Crisis” in Germany - Kapidzic, Sanja; Frey, Felix; Neuberger, Christoph; Stieglitz, Stefan; Mirbabaie, Milad (International Journal of Communication)
The study explores differences between three user types in the top tweets about the 2015 “refugee crisis” in Germany and presents the results of a quantitative content analysis. All tweets with the keyword “Flüchtlinge” posted for a monthlong period following September 13, 2015, the day Germany decided to implement border controls, were collected (N = 763,752). The top 2,495 tweets according to number of retweets were selected for analysis. Differences between news media, public and private actor tweets in topics, tweet characteristics such as tone and opinion expression, links, and specific sentiments toward refugees were analyzed. We found strong differences between the tweets. Public actor tweets were the main source of positive sentiment toward refugees and the main information source on refugee support. News media tweets mostly reflected traditional journalistic norms of impartiality and objectivity, whereas private actor tweets were more diverse in sentiments toward refugees.
Keywords: refugee crisis 2015; Germany; social media; Twitter; user types

Simulation-based investigation of the metrological interface structural resolution capability of X-ray computed tomography scanners - Busch, Matthias; Hausotte, Tino (Journal of Sensors and Sensor Systems)
Abstract. The miniaturisation of components leads to new demands on measurement systems. One of these is the resolution. As a volumetric analysis method and method of non-destructive testing, industrial X-ray computed tomography (XCT) has the ability to measure geometrical features and their corresponding dimensions without destroying them and can therefore be used for quality assurance. However, the concept of resolution is not trivial for XCT and has not yet been finally clarified. In particular, the interface structural resolution, the detectability of two surfaces facing each other after surface segmentation, faces a lack of a test specimen, a corresponding measurand and a reliable method. Simulation-based XCT investigations of a method to determine this type of resolution are presented in this article using the geometry of a test specimen that contains several radially arranged holes of the same size. The borehole diameters correspond to the distance between the holes to investigate the resolvability of surfaces and interfaces. The evaluation is based on mean and extreme values of grey value profiles between the individual boreholes of the reconstructed volume. It is shown that the geometrical detectability of the test specimen surface and interface can be extended by a reasonable choice of the threshold value for surface segmentation within a defined interval. With regard to the resolving capability, a distinction is made between assured detectability and possible detectability, as well as the threshold value used when using the ISO50 threshold for surface segmentation and measurement chain completion.
Keywords: Electrical and Electronic Engineering; Instrumentation

Location-Based Service and Location-Contextualizing Service: Conceptualizing the Co-creation of Value with Location Information - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Proceedings of the 56th Conference on System Sciences)

Mechanically Joined Extrusion Profiles for Battery Trays - Neumann, Stefan; Meschut, Gerson; Otroshi, Mortaza; Kneuper, Florian; Schulze, Andre; Tekkaya, Erman

How Virtuous are Virtual Influencers?–A Qualitative Analysis of Virtual Actors’ Virtues on Instagram - Hofeditz, Lennart; Erle, Lukas; Timm, Lara; Mirbabaie, Milad (Proceedings of the 55th Hawaii International Conference System Sciences (HICSS) (forthcoming))

Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Practice-Oriented Research in Tertiary Mathematics Education

Geographic Information Systems in Information Systems Research - Review and Research Prospects - Priefer, Jennifer (Proceedings of the 56th Hawaii International Conference on System Sciences)
Since historical times, cartographic maps have revealed spatial relations and enabled decisions and processes. Geographic Information Systems (GIS) allow for acquisition, management, analysis, and presentation of geospatial objects. With free geospatial data becoming available through open data policies and an increasing amount of digitally connected objects in the Internet of Things (IoT), GIS are becoming indispensable to Information Systems (IS) research. However, the consideration and relevance of GIS has only been investigated rarely. We examine, how and in which fields of application GIS have been studied in the IS literature and elicit the importance of GIS regarding their design and usage. A systematic literature review leads us to develop four research propositions. Our results indicate that GIS are still an undeservedly underrepresented discipline in IS and should be more theorized, put center-stage in design-oriented research, and considered for creating superior value co-creation in service systems.
Keywords: GIS; Industry 4.0; and Sustainability; geographic information systems; geospatial data; gis; information systems research; literature review

Examples of AI-based Assistance Systems in context of Model-Based Systems Engineering - Schrader, Elena; Bernijazov, Ruslan; Foullois, Marc; Hillebrand, Michael; Kaiser, Lydia; Dumitrescu, Roman (2022 IEEE International Symposium on Systems Engineering (ISSE))

Are Neural Bug Detectors Comparable to Software Developers on Variable Misuse Bugs? - Richter, Cedric; Haltermann, Jan Frederik; Jakobs, Marie-Christine; Pauck, Felix; Schott, Stefan; Wehrheim, Heike (37th IEEE/ACM International Conference on Automated Software Engineering)

Benchmark Fuzzing for Android Taint Analyses - Schott, Stefan; Pauck, Felix (2022 IEEE 22nd International Working Conference on Source Code Analysis and Manipulation (SCAM))

Scaling Arbitrary Android App Analyses - Pauck, Felix (37th IEEE/ACM International Conference on Automated Software Engineering)

Does Augmented Reality Help to Understand Chemical Phenomena during Hands-On Experiments?–Implications for Cognitive Load and Learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“ - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Experimentelle und modellbasierte Untersuchungen zum Prozessverhalten von teilkristallinen Materialien im Spritzgießsonderverfahren GITBlow - Kröker, Michael

Experimentelle Kompetenz Physikstudierender - Bauer, Anna Brigitte
Für den Erwerb fachmethodischer Fähigkeiten stellen Laborpraktika eine zentrale Lerngelegenheiten des Physikstudiums dar. Trotz ihrer hohen Bedeutung fehlt ein hochschulfachdidaktischer Diskurs zu einer lehr-lerntheoretischen Fundierung. Zudem wird ihre Lernwirksamkeit aufgrund der bestehenden didaktischen Gestaltung kritisiert. Die weit verbreiteten engmaschigen Aufgabenstellungen enthalten keine Anreize zur tiefergehenden Auseinandersetzung mit den Inhalten. Um der Diskrepanz zwischen den Zielsetzungen und den von den Lernenden erworbenen Fähigkeiten entgegenzuwirken, liegen aktuell nur wenige und zudem nur punktuelle Grundlagen für eine evidenzbasierte Überarbeitung dieses Veranstaltungsformates vor. Ziel dieser Arbeit ist daher, einen Vorschlag für ein performanzorientiertes Kompetenzstrukturmodell auf universitärem Niveau zu entwickeln, das die Inhaltsbereiche, die experimentellen Fähigkeiten und Fertigkeiten sowie die Qualitätsausprägungen experimenteller Handlungen systematisiert.Die Modellierung ist auf Basis der Analyse videografierter experimenteller Performanz von 16 unterschiedlich fähigen Proband:innen realisiert worden. Für die Entwicklung der Dimensionen Fachmethodik und Qualitätsausprägung werden unter Nutzung der qualitativen Forschungsansätze Dokumentarische Methode und Typenbildung die charakteristischen Merkmale universitären Experimentierens identifiziert und anschließend systematisiert. Zur Prüfung der Passung des Modells zur Perspektive der Wissenschaft Physik ist ein Interrating mit einem Fachwissenschaftler durchgeführt worden, das sehr gute Übereinstimmungswerte liefert. Die Passung des Modells zur Perspektive der Praktikumsleiter:innen ist durch ein Expertenrating erfolgt. Ein Rangfolgen-Vergleich zeigt hohe Übereinstimmungswerte.

Supporting Business Model Decision-making in B2B Ecosystems: A Framework for Using System Dynamics - Ksouri-Gerwien, C.; Vorbohle, Christian (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Literaturen vom 19. bis zum 21. Jahrhundert (thematische, ästhetische, mediale Transformationen hin zu einer technologisch aufgerüsteten Weltkommunikation) - Öhlschläger, Claudia (Grundthemen der Literaturwissenschaft: Weltliteratur.)

Anrisserkennung an geclinchten Proben während einer zyklischen Belastung unter Nutzung eines Scanning Laser Doppler Vibrometers - Brosius, Alexander; Ewenz, Lars; Stephan, Richard; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Ableitung flacher Probengeometrien zur Abbildung mehraxialer Spannungszustände in Clinchverbindungen unter zyklischer Beanspruchung - Ewenz, Lars; Kuczyk, Martin; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Untersuchungen zum Geometrie- und Frequenzeinfluss bei der Ermittlung zyklischer Kennwerte geclinchter Überlappverbindungen - Ewenz, Lars; Kühne, R.; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Verschränkung wie am Fließband - Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physik in unserer Zeit)

Rezension: Chiara Conterno / Astrid Dröse: Deutsch-italienischer Kulturtransfer im 18. Jahrhundert. Konstellationen, Medien, Kontexte - Süwolto, Leonie (DAJ)

Effekte eines Interventionsprogramms zur Förderung der sozialen Partizipation auf die Einstellungen von Grundschulkindern gegenüber Peers mit sonderpädagogischem Förderbedarf. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“. - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Consistent Optical and Electrical Noise Figure - Noé, Reinhold (Journal of Lightwave Technology)

Tschirk, Wolfgang. "Vom Universum des Denkens. Eine Geistesgeschichte der Logik". Springer: Berlin 2022, xvii, 117 S. - Peckhaus , Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C–F and S–F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Frustrated Lewis Pair Catalysed Reactions - Zhou, Rundong; Tavandashti, Zoleykha; Paradies, Jan (SynOpen)
In recent years, frustrated Lewis pairs have been widely used in small molecules activation and catalytic transformations. This graphic review is aimed to provide the fundamental understanding of frustrated Lewis pair reactivity and the exploitation thereof in catalytic reactions.
Keywords: Organic Chemistry; Materials Science (miscellaneous); Biomaterials; Catalysis

The association of chronotype and social jet lag with body composition in German students: The role of physical activity behaviour and the impact of the pandemic lockdown - Krueger, Betina; Stutz, Bianca; Jankovic, Nicole; Alexy, Ute; Kilanowski, Anna; Libuda, Lars; Buyken, Anette E. (PLOS ONE)
Young adults with a later chronotype are vulnerable for a discrepancy in sleep rhythm between work- and free days, called social jet lag (SJL). This study analysed (i) chronotype/SJL association with visceral fat/skeletal muscle mass, (ii) the attribution to physical activity behaviour, and (iii) chronotype-specific changes in physical activity behaviour in young adults during the Covid-19 pandemic lockdown. Chronotype and SJL were derived from the Munich-Chrono-Type-Questionnaire in 320 German students (age 18–25 years) from September 2019 to January 2020, 156 of these participated in an online follow-up survey in June 2020. Body composition was assessed by bioimpedance analysis at baseline. Multivariable linear regression analyses were used to relate chronotype/SJL to body composition; the contribution of self-reported physical activity was tested by mediation analysis. At baseline, a later chronotype and a larger SJL were associated with a higher visceral fat mass (P<0.05), this relation was notably mediated by the attention to physical activity (P<0.05). Chronotype (P = 0.02) but not SJL (P = 0.87) was inversely associated with skeletal muscle mass. During the pandemic lockdown, chronotype hardly changed, but SJL was reduced. Timing and physical activity behaviour remained in most participants and changes were unrelated to chronotype (all P>0.07). A later chronotype/higher SJL may increase the risk of a higher visceral fat mass even in this relatively healthy sample, which may be partly due to their physical activity behaviour. Despite a reduction in SJL during the pandemic lockdown, later chronotypes did not change their physical activity behaviour more than earlier chronotypes.
Keywords: Multidisciplinary

Politisch-humanistische Positionen in Reisenarrativen über Frankreich der 1920er und 1930er Jahre:„La lumière“ – Joseph Roths poetischer und medienreflexiver Humanismus - Öhlschläger, Claudia (Narrative des Humanismus in der Weimarer Republik und im Exil. Zur Aktualität einer kulturpolitischen Herausforderung für Europa.)

Including: Thinking Towards an Inclusive Curriculum for Technology Education in German Primary Schools - Schröer, Franz; Tenberge, Claudia (Bloomsbury Handbook of Technology Education)
Keywords: Curriculum; Inclusion; Sachunterricht; Participation

Enhancing Comprehension and Navigation in Jupyter Notebooks with Static Analysis - Shivarpatna Venkatesh, Ashwin Prasad; Wang, Jiawei; Li, Li; Bodden, Eric
Jupyter notebooks enable developers to interleave code snippets with rich-text and in-line visualizations. Data scientists use Jupyter notebook as the de-facto standard for creating and sharing machine-learning based solutions, primarily written in Python. Recent studies have demonstrated, however, that a large portion of Jupyter notebooks available on public platforms are undocumented and lacks a narrative structure. This reduces the readability of these notebooks. To address this shortcoming, this paper presents HeaderGen, a novel tool-based approach that automatically annotates code cells with categorical markdown headers based on a taxonomy of machine-learning operations, and classifies and displays function calls according to this taxonomy. For this functionality to be realized, HeaderGen enhances an existing call graph analysis in PyCG. To improve precision, HeaderGen extends PyCG's analysis with support for handling external library code and flow-sensitivity. The former is realized by facilitating the resolution of function return-types. Furthermore, HeaderGen uses type information to perform pattern matching on code syntax to annotate code cells. The evaluation on 15 real-world Jupyter notebooks from Kaggle shows that HeaderGen's underlying call graph analysis yields high accuracy (96.4% precision and 95.9% recall). This is because HeaderGen can resolve return-types of external libraries where existing type inference tools such as pytype (by Google), pyright (by Microsoft), and Jedi fall short. The header generation has a precision of 82.2% and a recall rate of 96.8% with regard to headers created manually by experts. In a user study, HeaderGen helps participants finish comprehension and navigation tasks faster. All participants clearly perceive HeaderGen as useful to their task.
Keywords: static analysis; python; code comprehension; annotation; literate programming; jupyter notebook

Die Schrift entHeiligen. Praktisch-theologische Überlegungen zum Bibelgebrauch als Transformation des Heiligen - Schroeter-Wittke, Harald (Heilige Schriften in der Kritik. XVII. Europäischer Kongress für Theologie (5.-8. September 2021 in Zürich). VWGTh 68)

Ostermontag (10.04.2023) Lk 24,13-35: Ostern to go! Oder: Wie Religionspädagogik geht - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Schule und Schulträger im Dialog: Gelingensbedingungen von Runden Tischen zur gemeinsamen Gestaltung des Digitalisierungsprozesses - Hagemann, L.; Herzig, Bardo; Möller-Glesemann, B. (Schulwelt NRW)

Updatable Privacy-Preserving Reputation System based on Blockchain - Pilot, Matthias

Epistemic Programming - Hüsing, Sven; Schulte, Carsten; Winkelnkemper, Felix (Computer Science Education)

Lehre in Zeiten von Digitalisierung und Inklusion – Beispiele aus drei Fächern. - Schmidt, Rebekka; Tenberge, Claudia; Häsel-Weide, Uta

Gathering a Euclidean Closed Chain of Robots in Linear Time and Improved Algorithms for Chain-Formation - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Knollmann, Till; Meyer auf der Heide, Friedhelm (Theoretical Computer Science)
Keywords: General Computer Science; Theoretical Computer Science

Distortional effects of separate accounting and formula apportionment on factor allocation - Ortmann, Regina; Pummerer, Erich (Journal of Business Economics)
Abstract We examine distortions caused by tax base allocation systems–separate accounting (SA) or formula apportionment (FA)–with respect to the allocation of assets and workforce within multinational entities (MNEs). The effects of both systems are intensively debated by EU Member States as they are striving to implement a European tax system. Its introduction would lead to a switch from SA to FA. Moreover, Pillar One of the recent global tax reform includes a mix of both tax base allocation systems. We find that, against the claims of the EU, FA does not necessarily create lower distortions of the factor allocation. Decisive for that assessment is the level of profit shifting under SA. Our results indicate that, in tendency, the factor allocation is more severely distorted by FA when the profit shifting possibilities were rather low under SA. In contrast to former studies, we highlight the importance of analyzing the status quo under the recently applied system (SA) in order to be able to assess the consequences of a switch from SA to FA. Our results are interesting for policy-makers as they help anticipating reactions of MNEs to a change in the applied tax base allocation system and for companies as a basis for future tax planning.
Keywords: Economics and Econometrics; Business and International Management

Die mündliche Prüfung. Eine Einführung - Matz, Frauke; Rogge, Michael; Rumlich, Dominik

Mechatronik und elektrische Antriebe / Mechatronics and electrical drives - Böcker, Joachim

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Model Generation For Java Frameworks - Luo, Linghui; Piskachev, Goran; Krishnamurthy, Ranjith; Dolby, Julian; Schäf, Martin; Bodden, Eric (IEEE International Conference on Software Testing, Verification and Validation (ICST))

Enhancing Comprehension and Navigation in Jupyter Notebooks with Static Analysis - Shivarpatna Venkatesh, Ashwin Prasad; Wang, Jiawei; Li, Li; Bodden, Eric (IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))

Immaterielles Kulturerbe in Nordrhein-Westfalen. Zur Bedeutung kultureller Ausdrucksformen - Harnack, Maria (Immaterielles Kulturerbe und regionale Identität – Schützenwesen in Deutschland)

Approaches to Improve Fairness when Deploying AI-based Algorithms in Hiring – Using a Systematic Literature Review to Guide Future Research - Rieskamp, Jonas; Hofeditz, Lennart; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the Annual Hawaii International Conference on System Sciences (HICSS))
Algorithmic fairness in Information Systems (IS) is a concept that aims to mitigate systematic discrimination and bias in automated decision-making. However, previous research argued that different fairness criteria are often incompatible. In hiring, AI is used to assess and rank applicants according to their fit for vacant positions. However, various types of bias also exist for AI-based algorithms (e.g., using biased historical data). To reduce AI’s bias and thereby unfair treatment, we conducted a systematic literature review to identify suitable strategies for the context of hiring. We identified nine fundamental articles in this context and extracted four types of approaches to address unfairness in AI, namely pre-process, in-process, post-process, and feature selection. Based on our findings, we (a) derived a research agenda for future studies and (b) proposed strategies for practitioners who design and develop AIs for hiring purposes.
Keywords: fairness in AI; SLR; hiring; AI implementation; AI-based algorithms

Deutscher Werkbund, Bauhaus, Hochschule für Gestaltung Ulm - Seng, Eva- Maria

Algorithmic Fairness in AI - Pfeiffer, Jella; Gutschow, Julia; Haas, Christian; Möslein, Florian; Maspfuhl, Oliver; Borgers, Frederik; Alpsancar, Suzana (Business & Information Systems Engineering)
Keywords: Information Systems